The Anatomy of Discretion: An Analysis of Prosecutorial Decision-making for Cases Processed by Offices in One Northern County and One Southern County, 2007-2010 - Frederick, Bruce ([Verlag nicht ermittelbar], 2015)
Prosecuting attorneys enjoy broad discretion in making decisions that influence criminal case outcomes. This study examines the impact of legal, quasi-legal, and extra-legal factors on case outcomes throughout the prosecutorial process. It then examines how prosecutors weigh these factors in their decision making and explores the formal and informal mechanisms that constrain or regulate prosecutors' decision-making. The study examines case screening decisions, charging decisions, plea offers, sentence recommendations, and dismissals in two moderately large county prosecutors' offices. It includes statistical analyses of actual case outcomes, responses to a standardized set of hypothetical cases, and responses to a survey of prosecutors' opinions and priorities, as well as qualitative analyses of two waves of individual interviews and focus groups. It addresses the following questions: How did prosecutors define and apply the concepts of justice and fairness? What factors were associated with prosecutorial outcomes at each stage? How did prosecutors interpret and weigh different case-specific factors in making decisions at each stage? How did contextual factors constrain or regulate prosecutorial decision making? How consistent were prosecutors' decisions across similar cases? What case-level and contextual factors influenced the degree of consistency?